Cyber-victimization among adolescents: its relationships with primary appraisal and coping strategies - Siah, Poh Chua; Tee, Xiang Yi; Yap, Chin Choo *; Tan, Chee Seng; Tan, Joanna Tjin Ai; Low, Sew Kim; Komathi, A. P Lokithasan (Taylor and Francis Group, 2022)
Cyber-victimization is prevalent among adolescents, but not all cyber-victims experience the same level of negative impacts. The individual difference can be related to their adopted coping strategies. By using the Transactional Model of Stress and Coping as a framework, it is expected that cyber-victims would appraise the bullying differently; which leads them to adopt different coping strategies. Cyber-victims are more likely to adopt passive coping strategies when they experience bullying from known bullies that they have frequent contact with. On the other hand, when they perceive that they have no future contact with the bullies, cyber-victims are more likely to adopt active coping strategies. In this study, school counsellors selected eighteen cyber-victims to participate in an in-depth interview using the purposive sampling method. The textual data was then analysed with thematic analysis. The results showed that this study identified some types of cyberbullying and coping strategies that are not covered in existing measurements; while participants are more likely to use passive strategies to cope with cyberbullying. More importantly, the findings revealed probable associations between known and unknown bullies and the use of active or passive coping strategies. The findings of this study indicate the importance of exploring the associations between primary and secondary appraisals as their relationships are seldom examined in cyber-victimization studies.